Effect of Cu-Ion Concentration in Concentrated H3PO4 Electrolyte on Cu Electrochemical Mechanical Planarization - Kung, Te-Ming; Liu, Chuan-Pu; Chang, Shih-Chieh; Chen, Kei-Wei; Wang, Ying-Lang (My University, 2010)
The influence of Cu-ion concentration in a concentrated H3PO4 electrolyte on the Cu removal rate and planarization efficiency (PE) of electrochemical mechanical planarization (ECMP) was investigated. With increasing Cu-ion concentration in the electrolyte, results show that the Cu removal rate significantly decreased because more Cu ions in the electrolyte facilitated the formation of a surface passive film. Electrochemical analysis shows that the current density decreased from 91 to 62 mA/cm(2) when the Cu-ion concentration was increased from 35.8 to 158.6 mM. In a low Cu-ion concentration electrolyte, Cu(OH)(2) is dominant, while in a high Cu-ion concentration electrolyte, CuO predominates. A high Cu-ion concentration in the electrolyte during ECMP promotes the formation of CuO, which retards Cu-ion diffusion from the Cu surface to the electrolyte solution, resulting in a decrease in the Cu removal rate. The intensity ratio of CuO/[Cu(OH)(2)+CuO] in the Cu 2p(3/2) X-ray photoelectron spectroscopy spectrum increased from 22.1 to 85.6% when the Cu-ion concentration was increased. The effect of Cu-ion concentration on the microscale PE of Cu ECMP is discussed. (C) 2010 The Electrochemical Society. [DOI: 10.1149/1.3425807] All rights reserved.
Keywords: copper; current density; diffusion; electrochemical analysis; electrolytes; hydrogen compounds; planarisation; X-ray photoelectron spectra